BLAZAR S5 0716+714: Variation of Linear Polarization - Amirkhanyan, V. R. (Astrophysical bulletin, 2022)
—From January 2019 to February 2021, observations of the linear polarization of the object S5 0716+714 were carried out with the Zeiss-600 telescope of SAO RAS. A Felix Savart plate was used as a polaroid. The result is a Fourier power spectrum of the linear polarization variation in the frequency range of – days without any harmonic component evidence; the spectrum is proportional to the power law . The distribution of polarization values over the entire observation period is subject to the Relay distribution which does not demonstrate any signs of a periodic component. There is a harmonic dependence of the polarization on the brightness of an object with a period of 10 mJy.